Differential analysis of serum immunology and gut microbiota in patients with gastrointestinal diseases - Chen, Huan Zhu; Zeng, Yu Yang; Cai, Guo Xiong; Gu, Wei Dan; Yang, YaLi (Frontiers in Microbiology, 2024)
Objective: Gastric and intestinal diseasespossess distinct characteristics although they are interconnected. The primary objective of this study was to investigate the pathogenesis of gastrointestinal diseases through different analyses of clinical characteristics, serum immunology, and gut microbiota in patients with gastrointestinal diseases. Methods: We collected serum samples from 89 patients with gastrointestinal diseases and 9 healthy controls for immunological assessment, stool samples for DNA extraction, library construction, sequencing, as well as clinical data for subsequent analysis. Results: Regarding clinical characteristics, there were significant differences between the disease group and the healthy control (HC) group, particularly in terms of age, cancer antigen 125 (CA125), cancer antigen 199 (CA199), alpha-fetoprotein (AFP), total bilirubin (TBIL) and indirect bilirubin (IBIL). The intestinal disease (ID) group exhibited the highest IL-6 level, which significantly differed from the stomach disease (SD) group (P<0.05). In comparing the HC with the ID groups, significant differences in abundance were detected across 46 species. The HC group displayed a greater abundance of Clostridiales, Clostridia, Firmicutes, Bifidobacterium, Bifidobacteriaceae, Bifidobacteriales, Actinobacteria, Veillonellaceae, Longum, Copri, Megamonas and Callidus than other species. Similarly, when comparing the HC with the SD groups, significant differences in abundance were identified among 49 species, with only one species that theLachnospiraceae in the HC group exhibited a higher abundance than others. Furthermore, certain clinical characteristics, such as CA125, CA199, glucose (Glu), creatine kinase-MB (CKMB) and interleukin-22 (IL-22), displayed positive correlations with enriched gut species in the ID and SD groups, while exhibiting a negative correlation with the HC group. Conclusion: The disturbance in human gut microbiota is intimately associated with the development and progression of gastrointestinal diseases. Moreover, the gut microbiota in the HC group was found more diverse than that in the ID and SD groups, and there were significant differences in microbial